Weight-bear specifics in patients with post traumatic extraarticular femoral and tibial fractures (statographic research) - Romanenko, Konstantin; Doluda, Yaroslav; Karpinsky, Mykhaylo; Prozorovsky, Dmytro (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2017)
An important component in the result of treatment of patients with posttraumatic deformities is the restoration of the wight-bearing ability of the damaged limb. Objective: to study the features of the wight-bearing ability patients with posttraumatic extraarticular deformities of the femur and shin bones according to statography. Methods: the results of standard statographic examinations were analyzed during a two-legged stance and with predominant support on each of the extremities of 38 patients, among whom 20 revealed bone fracture disorders and tibial deformity, 18 had femoral deformity. The duration of the deformation is from 3 to 15 months. Results: in patients with tibial deformations in the frontal plane, the common center of mass is shifted toward the intact limb and in patients with femoral deformity toward injured. In the sagittal plane, in patients with deformations of the tibia swings of the body in the frontal plane and in femur in the sagittal plane were noted. In single-bearing standing, patients with tibial deformity relied more on an intact limb and the displacement of the tibia was about 30 mm for both extremities (p < 0.05). In cases of femoral deformation, the difference between the shifts was almost 2 times (p < 0.05). A significant difference (p < 0.05) was found between the values of the scatter of the common center of mass and the scatter asymmetry coefficients in single-bearing standing in patients with deformations of tibia and femur. Reduction of the load on the affected limb was observed in all of the examined subjects. With the help of the analysis of statistical studies, a system was developed for assessing the patient’s initial condition and monitoring the process of his rehabilitation after surgical intervention. <span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: ’Times New Roman’; mso-fareast-font-family: ’Times New Roman’; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA;">Conclusions:<span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: ’Times New Roman’; mso-fareast-font-family: ’Times New Roman’; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;"> the analysis of the results of a statographic study of patients with extra-articular deformations of the tibia or femur performed prior to reconstructive intervention and in the dynamics after it allows to objectify the changes in the tolerance of the injured limb and to achieve a positive result of the treatment.